Personal factors and personal information activities behaviors of faculty in selected universities in Ghana - Donkor, A.B.; Nwagwu, W.E. (Library and Information Science Research, 2019)
This study examined how demographic characteristics of faculty influence their personal information activities behaviors, namely information creation, information organization, and information storage. Data was collected from a sample of 235 faculty in six universities in Ghana using a questionnaire. Age, gender, rank and university of affiliation predicted personal information activities behaviors in different directions and with different magnitudes. Gender made a difference in information organization and information storage while age made a difference in respect of information creation and information organization only. Faculty ages 4049 years created information the most, followed by those above 50 years. Males stored information more than females. Rank made a difference in information creation, organization and storage, but university of affiliation made a difference in information creation and information storage, and not information organization. It is common among information system designers and managers to implement information management systems without considering the differential influence of personal variables on human information behaviors. This omission denies information users adequate access and maximum use of the information in their information space. Institutional leaders and PIM systems designers should consider demographic and other personal factors of faculty in information literacy programs. Profiling of users' personal characteristics when designing personal information management systems will enhance maximum access and utilisation of personal information.
Research Article
Keywords: Personal information management (PIM); information storage; universities in Ghana; behaviors of faculty